2021
DOI: 10.1364/ol.442707
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage few-cycle nonlinear compression of milliJoule energy Ti:Sa femtosecond pulses in a multipass cell

Abstract: We report on the nonlinear temporal compression of mJ energy pulses from a Ti:Sa chirped pulse amplifier system in a multipass cell filled with argon. The pulses are compressed from 30 fs down to 5.3 fs, corresponding to two optical cycles. The post-compressed beam exhibits excellent spatial quality and homogeneity. These results provide guidelines for optimizing the compressed pulse quality and further scaling of multipass-cell-based post-compression down to the single-cycle regime.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 11 publications
0
17
0
1
Order By: Relevance
“…The postcompression in a multiple‐pass cell including a bulk plate or filled gas recently has been well studied for scaling pulse energy and accordingly peak‐ and average powers. [ 55–64 ] Figure 4c schematically shows that an input pulse is trapped in the Herriott cell for increasing its total propagation (interaction) length in a bulk plate (placed at foci) or filled gas. In this case, the B ‐integral, accordingly the self‐phase‐modulation‐induced spectrum broadening, increases with increasing the nonlinear propagating length, and after dispersion compensation, the output pulse can be compressed by 10 times.…”
Section: Ultrabroadband Pulse Generationmentioning
confidence: 99%
See 3 more Smart Citations
“…The postcompression in a multiple‐pass cell including a bulk plate or filled gas recently has been well studied for scaling pulse energy and accordingly peak‐ and average powers. [ 55–64 ] Figure 4c schematically shows that an input pulse is trapped in the Herriott cell for increasing its total propagation (interaction) length in a bulk plate (placed at foci) or filled gas. In this case, the B ‐integral, accordingly the self‐phase‐modulation‐induced spectrum broadening, increases with increasing the nonlinear propagating length, and after dispersion compensation, the output pulse can be compressed by 10 times.…”
Section: Ultrabroadband Pulse Generationmentioning
confidence: 99%
“…obtained millijoule‐level sixfold (30/5.3 fs) pulse compression also in a gas‐filled multiple‐pass cell. [ 62 ] One can find more progresses about this method in recent two review articles. [ 63,64 ]…”
Section: Ultrabroadband Pulse Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are interesting in the context of extending MPC for the post-compression of high average power, high repetition rate OPCPAs with pulse energies in the same range. Shortly after, Daniault et al demonstrated the compression of 30 fs, 1 mJ pulses from a Ti:Sapphire CPA down to 5.2 fs [106], extending implementation of MPC compression of Ti:Sapphire CPAs to the mJ energy range. A recent review about nonlinear pulse compression in MPCs can be found in [107].…”
Section: Post-compression Of High Power Cpasmentioning
confidence: 99%